Gold nanoparticles immobilised in a superabsorbent hydrogel matrix: facile synthesis and application for the catalytic reduction of toxic compounds. Issue 8 (6th January 2020) - Alzahrani, Hassan A. H.; Buckingham, Mark A.; Wardley, William P.; Tilley, Richard D.; Ariotti, Nicholas; Aldous, Leigh
Abstract : AuNP easily synthesised inside bulk hydrogel spheres; stable and catalytically active, even in high ionic strength environments. Abstract : Two methods are reported for the one-pot preparation of high concentrations of gold nanoparticles (AuNPs) embedded throughout sodium polyacrylate hydrogels; this stabilises the AuNP in even extremely high ionic strength environments, and enables them to act as effective catalysts for the hydride-reduction of nitrophenols and of dyes, with zero order kinetics.